Improving Instructional Leadership Through the Development of Leadership Content Knowledge: The Case of Principal Learning in Algebra - Steele, Michael D.; Johnson, Kate R.; Otten, Samuel; Herbel-Eisenmann, Beth A.; Carver, Cynthia L. (Journal of research on leadership education, 2015)
Instructional leadership is integral to improving mathematics teaching in secondary schools. However, administrators often lack sufficient content knowledge in mathematics to be effective in this role. This study examined the impact of professional development focused on developing leadership content knowledge in algebra. Data included written assessments, case discussions, and interviews from 10 principals. Analysis identified shifts in principals’ algebra content knowledge and their frames for interpreting algebra instruction. Principles improved their connections between mathematical representations and shifted from using frames highlighting teacher characteristics toward using frames highlighting teacher and student thinking. Implications for leadership professional development design are discussed.